PANDANGAN PASIEN MENGENAI TEKNIK MENGHARDIK PADA SAAT BERHALUSINASI DI RSJ PROVINSI JAWA BARAT TAHUN 2016 - Febrynia; Imelisa, Rahmi; Wisnusakti, Khrisna (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
The number of mental illness patient in West Java Province was 1.065.000 people or about 2,37 %citizen. Hallucination is one symptom used to diagnosed mental health illness: schizophrenia.Hearing and vision hallucination is the common type. Nowadays, techniques had been develop tocontrol hallucinations. This research aimed to explore patient viewpoint in conducting rebuketechnique when hallucination occurs in West Java Province Mental Health Hospital. This researchwas a qualitative research using phenomenology approach. Participants was selected withpurposive sampling techniques. The results showed that patients was able to revealed about theirhallucination of its contents, time of appearance, frequencies, provoke situations and their feelingswhile hallucinating. There was three themes obtained related to rebuke techniques, that was how toconduct, duration, and the advantage of rebuke techniques. It is expected that nurses can evaluatefuther about patient viewpoint about conducting rebuke techniques using different research methods.And another techniques to controll hallucination need to be considered.